2013
DOI: 10.5352/jls.2013.23.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Carthamus tinctorious Seed Extracts in Raw 264.7 cells

Abstract: The objective of this study was to evaluate the anti-inflammation effect of extract of Carthamus tinctorious seed, on skin obtained from Gyeong buk, Korea. Regulatory mechanisms of cytokines and nitric oxide (NO) involved in immunological activity of Raw 264.7 cells. Tested cells were pretreated with 70% ethanol extracted of Carthamus tinctorious seed and further cultured for an appropriated time after the addition of lipopolyssacharide (LPS). During the entire experimental period, 5, 10, 25 and 50 µg/ml of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…NO는 L-arginine을 기질로 하여 NOS에 의해서 합성되며 NO 가 과량으로 생성되면 염증 반응을 촉진시키고 조직 및 신경 을 손상시키는 것으로 알려져 있다 [14]. 발효톳 추출물의 NO 생성억제 활성을 알아보기 위해 RAW 264.7세포에서 LPS로 자극을 유도하고 시료를 농도별 (10, 100, 500 µg/mL) 로 처리하여 24시간 후 NO 생성량을 측정하였다 (Fig.…”
Section: 발효톳 추출물이 Lps에 의해 유도된 No 생성에 미치 는 영향unclassified
“…NO는 L-arginine을 기질로 하여 NOS에 의해서 합성되며 NO 가 과량으로 생성되면 염증 반응을 촉진시키고 조직 및 신경 을 손상시키는 것으로 알려져 있다 [14]. 발효톳 추출물의 NO 생성억제 활성을 알아보기 위해 RAW 264.7세포에서 LPS로 자극을 유도하고 시료를 농도별 (10, 100, 500 µg/mL) 로 처리하여 24시간 후 NO 생성량을 측정하였다 (Fig.…”
Section: 발효톳 추출물이 Lps에 의해 유도된 No 생성에 미치 는 영향unclassified
“…We previously demonstrated that the EtOAc fraction of Carthamus tinctorius seeds generated the highest inhibitory effect of inflammation among various extraction buffers, including 70% EtOH, n-hexane, ethyl acetate, and butyl alcohol (Kim et al 2013). In this study, partially purified EtOAc seed extract was further fractionated and major peaks were isolated using a modified method described by Kim et al (2012).…”
Section: Identification Of Four Major Chemical Compoundsmentioning
confidence: 99%
“…NO liberated from RAW 264.7 macrophages was measured using a Griess assay according to the method described by Kim et al (Kim et al 2013). The medium was subsequently mixed with an equal volume of Griess reagent (Sigma, St. Louis, MO, USA), after which the amount of NO was quantified by measuring the absorbance at 540 nm using a microplate reader and comparing the values to a sodium nitrite standard curve.…”
Section: Cell Culture and Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…따라서, 본 연구에서는 국산 생약 추 출물을 통해 염증 매개물질인 NO, IL-1β, IL-6, TNF-α의 생성을 억제하여 피부 자극반응을 예방할 수 있 는 화장품 소재로서 가능성을 검토하고자 하였다. [50], 치자(초) (Gardeniae Fructus) [51], 지황(Rehmaniae Radix crudus) [52], 홍화자(Cartami Semen) [53], 독활(Araliae Cordatae Radix) [54,55], 적작약(Paeoniae Radix rubra) [56], 복분 자(Rubi Fructus) [57], 건강(Zingiberis Rhizoma) [58], 고 본(Angelicae tenuissimae Radix) [59], 천궁(Cnidii Rhizoma) [60], 황기(Astragali Radix) [61] …”
unclassified